RISIKO SERANGAN STROKE AKIBAT PENYAKIT HIPERTENSI YANG TIDAK TERKONTROL: LAPORAN KASUS - Julaeha, Julaeha (Universitas 17 Agustus 1945 Jakarta, 2023)
Stroke is a neurological function disorder caused by cerebral blood circulation disorders. Stroke is the leading cause of long-term disability. Non-hemorrhagic stroke or ischemic stroke is 88% of all stroke cases. In this case, the stroke patient was 61 years old with a history of hypertension, hyperuricemia and after calculating the patient's Body Mass Index (BMI) of 34.78, it was included in the class I obesity range. The choice of hypertension drug plays a very important role in stabilizing the patient's stroke and if the blood clot in the brain is not repaired immediately then can lead to death. Drug Therapy Problems (DTPs) that occur in this case were the serious drug interactions between Amlodipine and Simvastatin and the major interactions between candesartan and piroxicam were in the pharmacokinetic phase and include major interactions.